2019
DOI: 10.1016/j.toxrep.2019.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Three (―)-cytisine derivatives and 1-hydroxyquinopimaric acid as acetylcholinesterase inhibitors

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…Cytisine derivatives have been explored as potential drugs against Alzheimer's and Parkinson's diseases as well as attention deficit hyperactivity disorder 2012 [4]. García-García et al studied in vitro acetylcholinesterase inhibition by cytisine derivatives [5]. Some studies have suggested that targeting the nicotinic acetylcholine receptors holds promise as a new therapeutic approach for the treatment of depression [6].…”
Section: Introductionmentioning
confidence: 99%
“…Cytisine derivatives have been explored as potential drugs against Alzheimer's and Parkinson's diseases as well as attention deficit hyperactivity disorder 2012 [4]. García-García et al studied in vitro acetylcholinesterase inhibition by cytisine derivatives [5]. Some studies have suggested that targeting the nicotinic acetylcholine receptors holds promise as a new therapeutic approach for the treatment of depression [6].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers can measure the activity of AChE in A. salina as an indicator of the potentially toxic effects of various substances. For example, if a substance inhibits the activity of AChE in A. salina , it may be a neurotoxin and could be harmful to other organisms, including humans [ 10 , 11 , 12 , 13 ]. This study is of paramount importance as it addresses gaps related to P. nigrum L., specifically the Guajarina cultivar.…”
Section: Introductionmentioning
confidence: 99%
“…Pesquisas relatam que produtos naturais e seus derivados são conhecidos por A reação de hidrólise da acetilcolina, catalisada pela enzima AChE (Figura 02) ocorre de forma natural no ser humano, cuja reação consiste em converter a acetilcolina nos produtos ácido acético e colina, por meio da hidrólise pela AChE(XU et al, 2019;IBRAHIM et al, 2009). A alta degradação de neurotransmissores, como a acetilcolina, em portadores da DA tem como consequência problemas de memória, comportamento e locomoção no indivíduo doente(GARCÍA-GARCÍA et al, 2019).…”
unclassified